2013
DOI: 10.1016/j.desal.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Boron removal and desalination from seawater by PVDF flat-sheet membrane through direct contact membrane distillation

Abstract: • PVDF flat-sheet membrane was prepared for boron removal and desalination.• The membrane had a narrow pore size distribution and exhibited good hydrophobicity.• Simultaneous boron removal and desalination from real seawater was carried out.• The influence of antiscalant on boron removal and desalination was investigated.• The prepared membrane was efficient for boron removal and desalination by DCMD. a b s t r a c t a r t i c l e i n f o Boron removal and desalination from seawater by direct contact membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…However, the salt rejection was higher than 99.9% under each operation temperature. Based on the performance under different temperature, a comparison with the flat-sheet membranes reported in the recent four years was carried out and listed in Table 6 [31,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. It can be found that the PVDF-CTFE membrane prepared in this work presented higher permeate flux in MD desalination application except PES and PSf membranes modified by CF4 plasma.…”
Section: Comparison With Other Flat-sheet MD Membranesmentioning
confidence: 99%
“…However, the salt rejection was higher than 99.9% under each operation temperature. Based on the performance under different temperature, a comparison with the flat-sheet membranes reported in the recent four years was carried out and listed in Table 6 [31,[48][49][50][51][52][53][54][55][56][57][58][59][60][61]. It can be found that the PVDF-CTFE membrane prepared in this work presented higher permeate flux in MD desalination application except PES and PSf membranes modified by CF4 plasma.…”
Section: Comparison With Other Flat-sheet MD Membranesmentioning
confidence: 99%
“…The pore size distribution and the liquid entry pressure, LEP, of each membrane were determined with a capillary flow porometer (Poroflux 1000, IB-GT GmbH, Germany) [50][51][52][53]. In addition, the chemical composition of each membrane surface was confirmed via polarization modulation-infrared reflection-adsorption spectroscopy, or PM-IRRAS (PMA 50, Bruker, Billerica, MA).…”
Section: Characterizations Of Morphology and Wetting Propertymentioning
confidence: 99%
“…Although B is required for all plant growth, at high levels B is toxic to plants and animals (1 to 2 m/L) [128]. Figure 11 shows the dissolved Si content in Fields A, B and C and is represented by a range of 13 -23 mg/L.…”
Section: Fluoride and Bromide Ionsmentioning
confidence: 99%
“…Pre-treatment methods for the removal of B prior to CS water being treated by RO may include adsorption or ion exchange. Adsorption as a treatment technology is limited by pH, temperature, and the properties of adsorbent used, however it is cost effective and can remove B to a low concentration (<0.05 mg/L) [128]. RO membranes and ion exchange together have also been found to be beneficial for B removal to reduce the cost associated with RO membranes alone [126].…”
Section: Fluoride and Bromide Ionsmentioning
confidence: 99%
See 1 more Smart Citation